1224. In vitro Activities of Ceftaroline and Comparator Agents against Gram-positive Bacterial Pathogens Causing Blood Stream Infections in a Global Population: ATLAS Surveillance Program 2012-2019. (4th December 2021) - Hackel, Meredith; Stone, Gregory; Sahm, Daniel F
Abstract: Background: Typical gram-positive organisms causing bloodstream infections (BSI) include Staphylococcus aureus (methicillin-susceptible [MSSA] and -nonsusceptible [MRSA]), coagulase negative staphylococci, Streptococcus pneumoniae and beta hemolytic streptococci. The parenteral cephem ceftaroline fosamil is approved for treatment of patients with community-acquired bacterial pneumonia caused by S. pneumoniae (including cases with concurrent bacteremia), MSSA, Haemophilus influenzae, and some species of Enterobacterales. Limited data have been published on the in vitro activity of ceftaroline against recent gram-positive clinical isolates known to be frequent bacterial causes of blood stream infections. Methods: Standard CLSI broth microdilution MIC determinations (M07) were performed with ceftaroline and comparator agents. MICs were interpreted using 2021 CLSI MIC breakpoints. Clinically relevant, non-duplicate, isolates cultured from blood by clinical laboratories in 2012-2019 were tested by the ATLAS (Antimicrobial Testing Leadership and Surveillance) program central laboratory (IHMA, Inc., Schaumburg, IL, USA). In total, 21, 967 non-duplicate isolates of S. aureus, S. epidermidis, S. pneumoniae and beta hemolytic streptococci from BSI collected between 2012 and 2019 were tested. Isolates came from (n/%): Asia/South Pacific (2, 970/13.5%), Europe (13, 691/62.3%), Latin America (2, 824/12.9%), MidEast/Africa (1, 498/6.8%), and North America (Canada only) (984/4.5%). Results: Ceftaroline and comparator agent activities are summarized in the following table. Results Table Conclusion: Greater than 99% of S. pneumoniae, beta-hemolytic streptococci and MSSA isolates included in a 2012-2019 collection of gram-positive blood stream pathogens were susceptible to ceftaroline. 90.8% of MRSA were susceptible, and 9.1% isolates categorized as susceptible-dose dependent (MIC, 2-4 µg/mL); four isolates (two from Thailand and one each from China and S. Korea) were resistant to ceftaroline (MIC >4 µg/mL). The ceftaroline MIC90 for S. epidermidis was 0.5 µg/mL, with 97.7% of MICs ≤1 µg/mL. Ceftaroline continues to demonstrate potent in vitro activity against clinically relevant pathogens associated with BSI. Disclosures: Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Gregory Stone, PhD, AztraZeneca (Shareholder, Former Employee)Pfizer, Inc. (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)